Technofinance Literacy, Financial Support and the Use of Bookkeeping Application on the Financial Behaviour - Alpiansah, Restu; Fitriyah, Nur; Lewandowski, Mariusz (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (Jebma), 2025)
This study is to investigate the impact of Technofinance Literacy, Financial Support, and the Use of Bookkeeping Applications on the Financial Behaviour of Generation Z in West Nusa Tenggara. Data were gathered using a quantitative methodology employing Partial Least Squares Structural Equation Modelling (PLS-SEM), with questionnaires administered to 246 eligible respondents. The analysis indicates that all three independent variables exert a positive and significant impact on financial behaviour. Financial support has the most significant influence, suggesting that persons who have financial assistance or supervision are more likely to exhibit responsible and organised financial behaviours. Technofinance literacy plays a crucial role, emphasising the necessity of comprehending and employing financial technologies for personal financial management. Moreover, the use of bookkeeping software, albeit with a diminished effect size, continues to significantly influence the development of disciplined financial habits. The findings indicate that integrating external assistance, technology literacy, and digital tools can significantly improve financial behaviour and should be incorporated into the development of educational or policy initiatives aimed at enhancing financial well-being among younger demographics.